Taboo as Oral Discourse and Cultural Code: Performative Communication of Moral and Ecological Values in Bugis Society - Suparman, Suparman; Abdullah Syukur; Tsamratul’aeni, Tsamratul’aeni (STAIN Majene, 2025)
This study aims at examining the phenomenon of taboo in Bugis society through an anthropolinguistic perspective. tTaboo is understood as a prohibition or taboo transmitted orally, functioning as a social, religious, and ecological mechanism to regulate behavior and to maintain communal harmony. By using a qualitative approach within the paradigm of linguistic ethnography, this research involved 12 key informants in Luwu Regency, South Sulawesi. Data were collected through participant observation, in-depth interviews, and documentation of taboo texts. The analysis was conducted through data reduction, thematic classification, and anthropological interpretation. The findings reveal four main dimensions of Bugis taboo: (1) religious integrating local customs with Islamic teachings; (2) social emphasizing ethics of mutual assistance and norms of interaction; (3) health-related particularly prohibitions concerning pregnant women and children; and (4) ecological functioning as local knowledge for natural resource conservation. Bugis taboo is shown to function not merely as an oral tradition, but also as a performative speech act that regulates behavior, instills moral values, and preserves local wisdom. These findings affirm the contribution of taboo as an important component of intangible cultural heritage while enriching cross-cultural studies of taboo.